RELIABILITY OF MODIFICATION QUESTIONNAIRE OF KNOWLEDGE LEVEL ABOUT ANEMIA IN ADOLESCENT - Putra, Kusuma Wijaya Ridi; Riesmiyatiningdyah, Riesmiyatiningdyah; Sulistyowati, Agus (Nurse and Holistic Care, 2021)
Introduction: The problem that is often experienced by young women is anemia. This anemia condition causes them to feel lethargic, dizzy, and a pale face. This situation causes them to be less eager to carry out activities and interfere with their learning concentration. Objective: This study aimed to determine the reliability test results of the questionnaire on the level of knowledge about anemia in adolescents. Methods: This study used a cross-sectional study method. This research was conducted on February 28, 2021. The study population was all adolescents in the Islamic Boarding School of Tahfizh Putri Alfirdaus Hidayatullah, Sekardangan, Sidoarjo. The sampling technique used was total sampling. The sample size of the study was 24 adolescents. This study used a modified questionnaire for adolescent knowledge about anemia (Zulaekah, 2007). The questionnaire used in this study only used 8 items from the original questionnaire. The data analysis carried out was Mean, Standard Deviation, and Cronbach's Alpha. Results: Based on the results of the reliability test on the adolescent knowledge level questionnaire, it was found that Cronbach's Alpha was .594. This illustrates that the questionnaire is good enough to be used as an instrument in research. Conclusion: A modified questionnaire about the level of adolescent knowledge about anemia can be used in a study.